Method for improving microstructure of catalyst layer of polymer electrolyte membrane fuel cell
By performing microwave heat treatment of polymer electrolyte membrane fuel cell catalytic layer, the albatrous lifts covered with the surface coverage, exposing more catalytic activity sites, solving the problem of low catalyst utilization, and improving the output performance of the fuel cell.
Patent Information
- Application Number
- CN202411512573.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In the existing polymer electrolyte membrane fuel cell catalytic layer, the catalyst surfactant site is masked or embedded by polymer ion conductors, resulting in large mass transfer resistance of O2 and ions through the catalyst-polymer interface and low catalyst utilization.
Microwave heat treatment technology is used to treat the catalytic layer to melt the ionomer covering its surface, improve the contact state between the polymer ion conductor and the catalyst, and expose more catalytically active sites.
Through microwave heat treatment, improve the accessability of O2 and ions, expose more catalytic activity sites, thereby improving the output performance of polymer electrolyte film fuel cells, and improving the utilization rate of catalysts.
Smart Images

Figure CN119361723A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer electrolyte membrane fuel cells, and in particular to a method for improving the microstructure of a catalyst layer of a polymer electrolyte membrane fuel cell. Background Art
[0002] The development and utilization of hydrogen energy, which has a wide range of sources and zero emissions, is a way to get rid of dependence on fossil energy and meets the country's major strategic needs. By 2030, the industry expects that the output value of my country's hydrogen energy industry will reach a trillion scale. However, as the most important carrier of the hydrogen energy industry, polymer electrolyte membrane fuel cells (PEMFCs) have been in a state of "lack of core" in key materials, among which the most important material is the catalyst. At present, the precious metal Pt / C is the most effective catalyst in the membrane electrode catalyst layer of PEMFCs, but the precious metal Pt has limited reserves on the earth and is expensive. Therefore, reducing the use of Pt in the catalyst layer is an urgent problem that needs to be solved for key materials of PEMFCs.
[0003] The traditional preparation method of the catalyst layer is mainly to mix and disperse the catalyst, binder and ion conductor in a dispersion medium to make a catalyst slurry, and then prepare the catalyst slurry on the gas diffusion layer or polymer electrolyte membrane by coating, spraying and casting. Obviously, in the catalyst layer prepared by the traditional method, the active sites on the catalyst surface are often covered or embedded by the polymer ion conductor, which increases the mass transfer resistance of O2 and ions in the catalyst layer through the catalyst-polymer interface, resulting in low catalyst utilization. Summary of the invention
[0004] In order to address the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a method for improving the microstructure of the catalyst layer of polymer electrolyte membrane fuel cells (PEMFCs), wherein the method uses microwave heat treatment technology to treat the catalyst layer, thereby melting the ionomer covered on the surface thereof, improving the contact state between the polymer ion conductor and the catalyst, improving the accessibility of O2 and ions, exposing more catalytic active sites, and thereby improving the output performance of PEMFCs.
[0005] The purpose of the present invention is achieved by the following technical solution: A method for improving the microstructure of a catalyst layer of a polymer electrolyte membrane fuel cell comprises the following steps:
[0006] (1) preparing catalyst slurry;
[0007] (2) coating the catalyst slurry on the carbon paper with the microporous gas diffusion layer; and then drying the carbon paper coated with the catalyst slurry to obtain the carbon paper with the catalyst layer;
[0008] (3) placing the carbon paper obtained in step (2) in a microwave reactor for microwave heating treatment;
[0009] (4) laminating one side of two microwave-heated carbon papers having a catalytic layer to two side surfaces of a polymer electrolyte membrane to obtain a first composite layer structure;
[0010] (5) sandwiching the first composite layer structure obtained in step (4) between two protective films to obtain a second composite layer structure; hot pressing the second composite layer structure, and then cooling it to obtain a membrane electrode with optimized structure.
[0011] Furthermore, in step (1), the catalyst and the polymer ion conductor are mixed, a dispersant is added, and ultrasonic treatment and stirring are performed to obtain a uniformly dispersed catalyst slurry.
[0012] Furthermore, in step (1), the catalyst is a Pt / C catalyst.
[0013] Furthermore, in step (1), the polymer ion conductor is a perfluorosulfonic acid polymer (Nafion solution); and the dispersant is at least one of methanol, ethanol, isopropanol and water.
[0014] Furthermore, in step (1), the mass ratio of the polymer ion conductor to the catalyst is 0.2-1.0.
[0015] Furthermore, in step (1), the dispersant is a water-isopropanol mixed dispersant, and the volume ratio of water to isopropanol is 0.1-10.
[0016] Furthermore, in step (1), the concentration of the catalyst in the dispersant is 2-4 mg / mL.
[0017] Furthermore, in step (2), the carbon paper coated with the catalyst slurry is vacuum dried for 2-18 hours, and the catalyst loading in the catalyst layer is calculated based on the mass difference of the carbon paper before and after the catalyst is sprayed.
[0018] Furthermore, in step (2), a perfluorosulfonic acid-based polymer layer is coated on the catalyst layer of the carbon paper.
[0019] Furthermore, in step (3), the microwave heating power is 200-1000W, and the microwave heating time is 2-30 minutes. In the present invention, after the carbon paper with the catalyst layer is subjected to microwave heating treatment by the above process, the Nafion layer wrapped on the surface of the catalyst in the catalyst layer is broken due to the microwave heat treatment, exposing more catalyst active sites, thereby improving the output performance of PEMFCs and effectively improving the utilization rate of the catalyst.
[0020] Furthermore, in step (3), the microwave heating atmosphere is nitrogen, argon and helium, and the microwave heating method is intermittent microwave heating, continuous microwave heating or a mixed heating method of intermittent microwave and continuous microwave.
[0021] Furthermore, in step (5), the hot pressing pressure is 0.2-1.0 MPa, the hot pressing temperature is 110-150° C., and the hot pressing time is 1-5 minutes.
[0022] The beneficial effects of the present invention are as follows: in order to solve the problems of large mass transfer resistance of O2 and ions through the catalyst-polymer interface and masking or embedding of active sites in the membrane electrode catalyst layer under actual working conditions of PEMFCs, the present invention adopts microwave heating treatment technology to treat the catalyst layer, so that the ionomer covering the surface can be melted, the accessibility of O2 and protons can be improved, more catalytic active sites can be exposed, and the output performance of PEMFCs can be improved; the method for improving the microstructure of the catalyst layer of the polymer electrolyte membrane fuel cell of the present invention is simple and controllable, and is suitable for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM electron microscope characterization image of the catalyst layer after structural optimization produced in Example 1.
[0024] Figure 2 The SEM and EDX element distribution images of the structurally optimized catalyst layer prepared in Example 1.
[0025] Figure 3 The oxygen reduction activity diagram and cyclic voltammetry curve of the catalyst layer half-cell after structural optimization produced in Example 1 are shown.
[0026] Figure 4 is the fuel cell polarization curve of the membrane electrode prepared in Example 1. DETAILED DESCRIPTION
[0027] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0028] In an embodiment of the present invention, a method for improving the microstructure of a catalyst layer of a polymer electrolyte membrane fuel cell comprises the following steps:
[0029] (1) preparing catalyst slurry;
[0030] (2) coating the catalyst slurry on the carbon paper with the microporous gas diffusion layer; and then drying the carbon paper coated with the catalyst slurry to obtain the carbon paper with the catalyst layer;
[0031] (3) placing the carbon paper obtained in step (2) in a microwave reactor for microwave heating treatment;
[0032] (4) placing two pieces of carbon paper that have been subjected to microwave heating treatment on two sides of the polymer electrolyte membrane, respectively, and laminating one side of the two pieces of carbon paper having the catalyst layer to the two sides of the polymer electrolyte membrane, respectively, to obtain a first composite layer structure;
[0033] (5) The first composite layer structure obtained in step (4) is sandwiched between two PTFE protective films to obtain a second composite layer structure; the second composite layer structure is hot pressed and then cooled to obtain a membrane electrode with optimized structure.
[0034] Furthermore, in step (1), the catalyst and the polymer ion conductor are mixed, a dispersant is added, and ultrasonic treatment and stirring are performed to obtain a uniformly dispersed catalyst slurry.
[0035] Furthermore, in step (1), the catalyst is a Pt / C catalyst. The catalyst may be commercial carbon-supported Pt (Pt / C), and the Pt loading of the catalyst is 0.1 to 2.0 mg. Pt / cm 2 .
[0036] Furthermore, in step (1), the polymer ion conductor is a perfluorosulfonic acid polymer. The perfluorosulfonic acid polymer is also used as a binder. The dispersant is at least one of methanol, ethanol, isopropanol and water.
[0037] In some embodiments of the present invention, in step (1), the mass ratio of the polymer ion conductor to the catalyst is 0.2-1.0.
[0038] In some embodiments of the present invention, in step (1), the dispersant is a water-isopropanol mixed dispersant, and the volume ratio of water to isopropanol is 0.1-10.
[0039] In some embodiments of the present invention, in step (1), the concentration of the catalyst in the dispersant is 2-4 mg / mL.
[0040] In some embodiments of the present invention, in step (2), the carbon paper coated with the catalyst slurry is vacuum dried for 2-18 hours, and the catalyst loading in the catalyst layer is calculated based on the mass difference of the carbon paper before and after the catalyst is sprayed.
[0041] The method of coating the catalyst slurry on the microporous gas diffusion layer or the polymer electrolyte membrane in the present invention can adopt spraying, casting, scraping and other methods.
[0042] In some embodiments of the present invention, in step (2), after the carbon paper is dried, a perfluorosulfonic acid-based polymer layer is coated on the catalyst layer of the carbon paper.
[0043] In some embodiments of the present invention, in step (3), the microwave heating power is 200-1000 W, and the microwave heating time is 2-30 minutes.
[0044] In some embodiments of the present invention, in step (3), the microwave heating atmosphere adopts nitrogen, argon and helium, and the microwave heating method adopts intermittent microwave heating method, continuous microwave heating method or intermittent microwave and continuous microwave mixed heating method.
[0045] Example 1
[0046] In this embodiment, a method for improving the microstructure of a catalyst layer of a polymer electrolyte membrane fuel cell comprises the following steps:
[0047] (1) 30.0 mg of Pt / C catalyst was added with 2.00 mL of deionized water, 1.00 mL of 5 wt% Nafion solution, and 8.00 mL of isopropanol, and ultrasonic treatment and stirring were performed to obtain a catalyst slurry;
[0048] (2) spraying the catalyst slurry onto the carbon paper with the microporous gas diffusion layer; then drying the carbon paper sprayed with the catalyst slurry to obtain the carbon paper with the catalyst layer;
[0049] (3) placing the carbon paper obtained in step (2) in a microwave reactor and performing microwave heating treatment, the microwave heating power is 900 W, the microwave heating time is 30 minutes, and the carbon paper with optimized catalytic layer microstructure is obtained. The scanning electron microscope image and element distribution are as follows: Figure 1-2 As shown;
[0050] (4) placing two pieces of carbon paper that have been subjected to microwave heating treatment on two sides of the polymer electrolyte membrane, respectively, and laminating one side of the two pieces of carbon paper having the catalyst layer to the two sides of the polymer electrolyte membrane, respectively, to obtain a first composite layer structure;
[0051] (5) The first composite layer structure obtained in step (4) is sandwiched between two PTFE protective films to obtain a second composite layer structure; the second composite layer structure is hot pressed and then cooled to obtain a membrane electrode with optimized structure.
[0052] Furthermore, in step (2), the carbon paper coated with the catalyst slurry was vacuum dried for 10 hours. The catalyst loading in the catalyst layer was calculated based on the mass difference of the carbon paper before and after the catalyst was sprayed. The Pt loading in the catalyst layer was 0.2 mg / cm 2 .
[0053] Furthermore, in step (3), the microwave heating atmosphere is nitrogen, the microwave heating method is a continuous microwave heating method, and the carbon paper with the catalytic layer is placed in a microwave reactor for heating.
[0054] Furthermore, in step (5), the hot pressing pressure is 0.5 MPa, the hot pressing temperature is 130° C., and the hot pressing time is 2 minutes.
[0055] In this embodiment, Figure 1 The SEM electron microscope characterization image of the catalyst layer after structural optimization produced in this embodiment shows that after microwave heating, the Nafion wrapped on the surface of the catalyst in the catalyst layer melts and cracks.
[0056] Figure 2 The SEM and EDX element distribution diagrams of the catalyst layer after structural optimization prepared according to this embodiment are shown in FIG. Figure 2 a is the SEM image, Figure 2 b, c, and d are the element distribution diagrams of F, C, and Pt elements, respectively. It can be seen that after microwave treatment, there is no obvious enrichment of C and Pt elements, while F element is obviously enriched at the edge of the crack, indicating that the F-containing Nafion layer is broken due to microwave heat treatment, exposing more catalyst active sites.
[0057] In 0.1 mol / L perchloric acid solution, a three-electrode system was used to test the redox reaction performance of carbon paper with a catalytic layer before and after microwave treatment. The test results are as follows: Figure 3 shown. Figure 3 The oxygen reduction activity diagram and cyclic voltammetry curve of the catalyst layer half-cell after structural optimization made in this embodiment are shown in FIG. Figure 3 It can be seen that after 30 minutes of microwave heat treatment, the current density of the optimized catalyst layer at 0.2V vs. RHE reached 51.43mA / cm 2 , which is higher than the untreated catalytic layer (40.87 mA / cm 2 , at 0.2V vs.RHE). Figure 3 The electrochemical active area (ECSA) of the catalyst was calculated from the cyclic voltammetry curve of b. The ECSA of the catalyst layer after microwave heat treatment for 30 minutes reached 68.75 m 2 / g, which is higher than the ECSA (36.64m 2 / g).
[0058] Two carbon papers with optimized catalyst layer microstructure, polymer electrolyte membrane and two PTFE protective membranes were hot pressed together to form membrane electrodes, and the performance of a single fuel cell was tested. The hydrogen flow rate was 200sccm, the oxygen flow rate was 300sccm, both hydrogen and oxygen were 100% humidified, the back pressure was 0.1MPa, and the battery operating temperature was 70℃. The measured results are as follows Figure 4 shown. Figure 4 The polarization curve of the fuel cell membrane electrode prepared according to this embodiment shows that the performance of the fuel cell membrane electrode of the catalyst layer after 30 minutes of microwave heat treatment is greatly improved, and the maximum power density reaches 1.29W / cm 2 , while the corresponding membrane electrode peak power density of the untreated catalyst layer is 1.14W / cm 2 .
[0059] Example 2
[0060] In this embodiment, a method for improving the microstructure of a catalyst layer of a polymer electrolyte membrane fuel cell comprises the following steps:
[0061] (1) 30.0 mg of Pt / C catalyst was added with 2.00 mL of deionized water, 1.00 mL of 5 wt% Nafion solution, and 8.00 mL of isopropanol, and ultrasonic treatment and stirring were performed to obtain a catalyst slurry;
[0062] (2) spraying the catalyst slurry onto the carbon paper with the microporous gas diffusion layer; then drying the carbon paper sprayed with the catalyst slurry to obtain the carbon paper with the catalyst layer;
[0063] (3) placing the carbon paper obtained in step (2) in a microwave reactor and performing microwave heating treatment, the microwave heating power is 900 W, the microwave heating time is 30 minutes, and the carbon paper with optimized catalytic layer microstructure is obtained. The scanning electron microscope image and element distribution are as follows: Figure 1-2 As shown;
[0064] (4) placing two pieces of carbon paper that have been subjected to microwave heating treatment on two sides of the polymer electrolyte membrane, respectively, and laminating one side of the two pieces of carbon paper having the catalyst layer to the two sides of the polymer electrolyte membrane, respectively, to obtain a first composite layer structure;
[0065] (5) The first composite layer structure obtained in step (4) is sandwiched between two PTFE protective films to obtain a second composite layer structure; the second composite layer structure is hot pressed and then cooled to obtain a membrane electrode with optimized structure.
[0066] Furthermore, in step (2), the carbon paper coated with the catalyst slurry was vacuum dried for 10 hours. The catalyst loading in the catalyst layer was calculated based on the mass difference of the carbon paper before and after the catalyst was sprayed. The Pt loading in the catalyst layer was 0.2 mg / cm 2 .
[0067] The rest of the content of this embodiment is similar to that of Embodiment 1 and will not be repeated here.
[0068] Example 3
[0069] In this embodiment, a method for improving the microstructure of a catalyst layer of a polymer electrolyte membrane fuel cell comprises the following steps:
[0070] (1) 30.0 mg of Pt / C catalyst was added with 1.00 mL of deionized water, 0.50 mL of 5 wt% Nafion solution, and 9.50 mL of isopropanol, and ultrasonic treatment and stirring were performed to obtain a catalyst slurry;
[0071] (2) Spraying the catalyst slurry onto the carbon paper with the microporous gas diffusion layer; then drying the carbon paper sprayed with the catalyst slurry to obtain the carbon paper with the catalytic layer; spraying a layer of Nafion on the catalytic layer of the carbon paper; spraying a layer of Nafion can improve the ionic conductivity, improve the gas transmission, optimize the three-phase interface and regulate the microstructure of the catalytic layer.
[0072] (3) placing the carbon paper obtained in step (2) in a microwave reactor and performing microwave heating treatment at a microwave heating power of 900 W and a microwave heating time of 30 minutes to obtain carbon paper with optimized catalytic layer microstructure;
[0073] (4) placing two pieces of carbon paper that have been subjected to microwave heating treatment on two sides of the polymer electrolyte membrane, respectively, and laminating one side of the two pieces of carbon paper having the catalyst layer to the two sides of the polymer electrolyte membrane, respectively, to obtain a first composite layer structure;
[0074] (5) The first composite layer structure obtained in step (4) is sandwiched between two PTFE protective films to obtain a second composite layer structure; the second composite layer structure is hot pressed and then cooled to obtain a membrane electrode with optimized structure.
[0075] Furthermore, in step (2), the carbon paper coated with the catalyst slurry was vacuum dried for 10 hours. The catalyst loading in the catalyst layer was calculated based on the mass difference of the carbon paper before and after the catalyst was sprayed. The Pt loading in the catalyst layer was 0.2 mg / cm 2 .
[0076] The rest of the content of this embodiment is similar to that of Embodiment 1 and will not be repeated here.
[0077] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations of the implementation methods. For those skilled in the art, any obvious replacements that do not depart from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A method for improving the microstructure of a catalyst layer of a polymer electrolyte membrane fuel cell, characterized in that: The steps include: (1) preparing catalyst slurry; (2) coating the catalyst slurry on the carbon paper with the microporous gas diffusion layer; and then drying the carbon paper coated with the catalyst slurry to obtain the carbon paper with the catalyst layer; (3) placing the carbon paper obtained in step (2) in a microwave reactor for microwave heating treatment; (4) laminating one side of two microwave-heated carbon papers having a catalytic layer to two side surfaces of a polymer electrolyte membrane to obtain a first composite layer structure; (5) sandwiching the first composite layer structure obtained in step (4) between two protective films to obtain a second composite layer structure; The second composite layer structure is hot pressed and then cooled to obtain a membrane electrode with optimized structure.
2. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (1), the catalyst and the polymer ion conductor are mixed, a dispersant is added, and ultrasonic treatment and stirring are performed to obtain a uniformly dispersed catalyst slurry.
3. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (1), the catalyst is a Pt / C catalyst; the polymer ion conductor is a perfluorosulfonic acid polymer; and the dispersant is at least one of methanol, ethanol, isopropanol and water.
4. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (1), the mass ratio of the polymer ion conductor to the catalyst is 0.2-1.
0.
5. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (1), the dispersant is a water-isopropanol mixed dispersant, and the volume ratio of water to isopropanol is 0.1-10.
6. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (2), the carbon paper coated with the catalyst slurry is vacuum dried for 2-18 hours. The catalyst loading in the catalyst layer is calculated based on the mass difference of the carbon paper before and after the catalyst is sprayed.
7. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (2), a perfluorosulfonic acid-based polymer layer is coated on the catalyst layer of carbon paper.
8. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (3), the microwave heating power is 200-1000W, and the microwave heating time is 2-30 minutes.
9. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (3), the microwave heating atmosphere is nitrogen, argon and helium, and the microwave heating method is intermittent microwave heating, continuous microwave heating or a mixed heating method of intermittent microwave and continuous microwave.
10. The method for improving the microstructure of the catalyst layer of a polymer electrolyte membrane fuel cell according to claim 1, characterized in that: In step (5), the hot pressing pressure is 0.2-1.0 MPa, the hot pressing temperature is 110-150° C., and the hot pressing time is 1-5 minutes.
Citation Information
Patent Citations
Fuel cell catalyst slurry and application thereof
CN104716342A
Preparation method of catalyst layer for improving performance of proton exchange membrane fuel cell
CN109860636A
Catalyst for fuel cell using metal complex composite, membrane electrode assembly, fuel cell, and oxidation-reduction catalyst
JP2010015970A
Paste for electrode of fuel cells, membrane electrode assembly, and method for manufacturing paste for electrode
JP2010161004A
Electrode for fuel cell, fuel cell comprising thesame, and method for preparing the smme
KR1020060058919A